Contribution to Improvement of Fatigue Properties of Zr-4 Alloy: Gradient Nanostructured Surface Layer versus Compressive Residual Stress - Donghui Geng; Qiaoyan Sun; Chao Xin; Lin Xiao (Nanomaterials, 2021)
The gradient nanostructured (GNS) layer forms beneath the surface of Zr-4 samples by the surface mechanical grinding treatment (SMGT) process, which increases the fatigue strength apparently due to the synergistic effect of the gradient nanostructured layer and compressive residual stress. The SMGTed Zr-4 samples are subjected to annealing to remove residual stress (A-SMGT) and the individual effect of the GNS layer and compressive residual stress can be clarified. The results show that the gradient nanostructure in the surface is stable after annealing at 400 °C for 2 h but residual stress is apparently removed. Both SMGTed and A-SMGTed Zr-4 samples exhibit higher fatigue strength than that of coarse-grained (CG) Zr-4 alloy. The fatigue fracture of Zr-4 alloy indicates that the hard GNS surface layer hinders fatigue cracks from approaching the surface and leads to a lower fatigue striation space than that of CG Zr-4 samples. The offset fatigue strength of 106 cycles is taken for SMRT-ed, A-SMRT-ed, and CG Zr-4 samples and the results indicate clearly that the GNS surface layer is a key factor for the improvement of fatigue strength of the Zr-4 alloy with surface mechanical grinding treatment.